Prevalence of dental caries and associated factors among school-aged children in Tripoli, Libya: a cross-sectional study - Hosam Alraqiq; Ahmid Eddali; Reema Boufis (BMC, 2021)
Abstract Background In many developing countries, the prevalence of dental caries has increased due to lifestyle changes, lack of preventive services, and inadequate access to dental care. In Arab countries, the increased prevalence of caries has correlated with economic growth over the past decades, resulting in greater access to unhealthy foods and higher consumption of sugar, particularly among children. However, few studies have assessed caries prevalence among pediatric populations in Arab countries. The objective of this study was to assess the prevalence of dental caries and factors associated with caries among children in Tripoli, Libya. Methods This cross-sectional study included a convenience sample of 1934 children in first grade (age 6-7 years, n = 1000) and seventh grade (age 11-12 years, n = 934). Four health centers in Tripoli were selected for screening based on location and participation in school-entry health examinations. Data were collected through self-administered parent surveys and visual dental screenings by trained examiners from September 24 to October 15, 2019. The survey comprised questions about socioeconomic characteristics and oral health behaviors, including toothbrushing, sugar consumption, and dental care history. During screenings, untreated decay, missing teeth, and filled teeth (DMFT or dmft) were recorded. Prevalence of tooth decay was calculated as the proportion of children with high DMFT/dmft scores. Binary logistic and negative binomial regression analyses (with significance at p ≤ 0.05) were used to assess factors associated with caries. Results Among 1000 first-grade children, 78.0% had decay in their primary teeth, with a mean dmft of 3.7. Among 934 seventh-grade children, 48.2% had caries in their permanent teeth, with a mean DMFT of 1.7. The most significant factors associated with caries prevalence were socioeconomic, such as screening site (first grade, p = 0.02; seventh grade, p < 0.001) and maternal employment (seventh grade, p = 0.02), and behavioral, such as toothbrushing duration (seventh grade, p = 0.01), past dental treatment (both grades, p < 0.001), and past emergency visit (both grades, p < 0.001). Conclusions Caries prevalence was associated with several behavioral and socioeconomic factors, including screening site, maternal employment, toothbrushing duration, past dental treatment, and past emergency visit. Efforts should be made to address these factors to minimize barriers and improve oral health behavior and care utilization. These findings can be used to evaluate current public health initiatives and inform future planning.